Early-Onset Parkinson's Disease Caused by PLA2G6 Compound Heterozygous Mutation, a Case Report and Literature Review - Shen, Ting; Hu, Jing; Jiang, Yasi; Zhao, Shuai; Lin, Caixiu; Yin, Xinzhen; Yan, Yaping; Pu, Jiali; Lai, Hsin-Yi; Zhang, Baorong (Frontiers in Neurology, 2019)
PLA2G6 has been certified as a causative gene in patients with autosomal recessive early-onset Parkinson's disease (EOPD). We reported an EOPD case caused by PLA2G6 gene mutation, and performed neurological examination, genetic analysis and multimodal neuroimaging to describe this phenotype. A compound heterozygous mutation c.991G>T/c.1472+1G>A was detected in this patient. Heterozygous for the c.991G>T and c.1472+1G>A were separately detected in his parents. Pathogenicity of these two mutations were predicted according to the American college of medical genetics and genomics (ACMG) guideline. MRI assessment showed absence of bilateral “swallow tail sign” and cerebellar atrophy in this patient, while no obvious difference in brain iron accumulation between PLA2G6 mutant PD patient and healthy controls. Cerebellar abnormalities may be a marker for diagnosis and evaluation of PLA2G6 mutation Parkinsonism. However the iron accumulation in PD may not be the result of PLA2G6 mutation.